Identifikasi Source Credibility, Homophily dan Content Quality dari Konsumen Produk Fashion dalam Perilakunya di Media Sosial - Yuski Adristia, Ivan; Ratna Roostika, Raden Roro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of social media interaction on purchase intention through several factors, namely source credibility, homophily, and content quality on Erigo local fashion products. The population in this study are people Yogyakarta who actively use Instagram social media and are familiar with Erigo products aged less than 20 years to 40 years and over who live in Yogyakarta. The research sample used in this study was 234 respondents obtained through an online survey and analyzed using Smart PLS software with the PLS-SEM method. Based on the results, it is known that social media interaction has a positive effect on source credibility, homophily, and content quality. Homophily and content quality have a positive effect on purchase intention. However, source credibility has a negative effect on purchase intention. Through this study, it is hoped that it can add to the marketing literature on purchase intentions through interactions that occur on social media and. This study also recommends that marketers pay attention to factors that can influence consumers in making purchasing decisions.